Effectiveness of Scaffolding Technique in Scientific Learning Model on Students Mathematics Critical Thinking Skills and Self-Regulated Learning - Lalu Irfan Abdul Manaf; Dhoriva Urwatul Wutsqa; Ramadian Radite (STAI Hubbulwathan Duri, 2024)
This study examines the effectiveness of a scientific learning model incorporating scaffolding techniques on students' critical thinking skills and self-regulated learning, as well as identifying contributing factors to its success. A mixed-methods approach with a quasi-experimental design was applied, involving 62 students randomly selected from two groups in a State Senior High School in Praya Regency. Critical thinking skills were assessed using essay tests based on defined indicators, while self-regulated learning data were collected through questionnaires. Observations of learning activities aligned with the lesson plan provided qualitative data. Quantitative data were analyzed using multivariate inferential analysis, while qualitative data were triangulated between observations and test results. The findings demonstrate that the scientific learning model with scaffolding techniques significantly enhances students' critical thinking skills and self-regulated learning compared to models without scaffolding. Scaffolding techniques, such as providing examples during observation, guiding questioning, modeling reasoning, and supporting communication through reporting findings, foster independent critical thinking habits. The results highlight the importance of scaffolding in guiding students through the stages of scientific learning. By systematically supporting their learning processes, students become better equipped to think critically and regulate their learning independently. The scientific learning model with scaffolding techniques is effective in improving critical thinking and self-regulated learning. Future research should explore its application across varied subjects and educational contexts to generalize its impact.